Imagens dos objetos das Transferências Voluntárias da União em mapas - Diego Tenório da Paz (Confins)
This essay comments on images that present the situation of Union Voluntary Transfers (TVU) in Brazil, which are financial resources intended for the execution of projects with infrastructure objects and/or services carried out by subnational entities. This is a discussion proposed and developed within the scope of academic doctorate research that analyzes the relationship between planning, policy and territory.